Public Relations and Advertising Theories: Concepts and Practices - Aydin, Bayram Oguz; Sahin, Emine; Dugan, Özlem (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
The main goal of this book is to draw attention to possible applications of public relations and advertising theories. The authors aim to present a new perspective for public relations and advertising research, claiming that it is worth looking at what theories are used in public relations and advertising space. This book provides an overview of key studies and contributions to the theories, as well as explores how the theoretical concepts can be applied in public relations. The practical solutions set out in this book focus on various public and private sectors. The studies analysed and the applications proposed are particularly valuable in terms of how public relations and advertising theories respond in practice. For this reason, this book will be an important work both for academics and practitioners working in the field of public relations and advertising.
Keywords: reklama a propagace; public relations; advertising; elektronické knihy; electronic books